Silicon nanocrystals: Novel synthesis routes for photovoltaic applications. Issue 4 (18th October 2012) - Perraud, Simon; Quesnel, Etienne; Parola, Stéphanie; Barbé, Jérémy; Muffato, Viviane; Faucherand, Pascal; Morin, Christine; Jarolimek, Karol; Van Swaaij, René A. C. M. M.; Zeman, Miro; Richards, Stephen; Kingsley, Andrew; et al.
Abstract Novel processes were developed for fabricating silicon nanocrystals and nanocomposite materials which could be used as absorbers in third generation photovoltaic devices. A conventional high‐temperature annealing technique was studied as a reference process, with some new insights in crystallisation mechanisms. Innovative methods for silicon nanocrystal synthesis at much lower temperature were demonstrated, namely chemical vapour deposition (CVD), physical vapour deposition (PVD) and aerosol‐assisted CVD. Besides the advantage of low substrate temperature, these new techniques allow to fabricate silicon nanocrystals embedded in wide bandgap semiconductor host matrices, with a high density and a narrow size dispersion.